Assessing healthcare payment reforms’ effects on economic inequities and catastrophic expenditures among cancer patients in ethnic minority regions of China - Xin Xiang; Yu Li; Ning Liang; Bangqin Wang; Hongzhi Wang (BMC Medicine)
Abstract Background Ethnic minority groups are particularly vulnerable to healthcare inequities, with catastrophic medical expenditures often pushing them into poverty. However, empirical research on the impact of healthcare reforms on these populations remains limited. This study aims to address this gap by exploring the effects of healthcare payment reforms on healthcare outcomes and financial protection during serious illnesses among ethnic minority populations. Methods A cross-sectional study was conducted using data from three major ethnic minority groups in China: the Zhuang, Hui, and Manchu. The analysis is based on hospitalization data from 59,622 ethnic minority cancer patients spanning from 2013 to 2024. Ordinary least squares (OLS) linear regression was employed to assess the effects of healthcare payment reforms on healthcare expenses and cost-sharing. Results The findings indicate that, compared to traditional payment methods, the implementation of diagnosis-related group (DRG) payment reforms led to reductions in hospitalization, drug, and treatment expenses for ethnic minority patients. However, a closer examination of the cost structure reveals that while DRG payment systems have reduced expenditures for public health insurance fund, they have simultaneously increased out-of-pocket costs for minority patients. Conclusions Given that many ethnic minority patients belong to economically disadvantaged groups with limited financial resources, the rise in out-of-pocket costs exacerbates their economic burden, making them more vulnerable to catastrophic medical expenditures. This situation poses a severe challenge to minority patients already in precarious financial circumstances. This study offers insights and lessons from China that may guide governments worldwide in mitigating healthcare inequities faced by vulnerable populations.